IMPLEMENTASI PASAL 8 (4) PERATURAN MENTERI DALAM NEGERI NO. 114 TAHUN 2014 TENTANG PARTISIPASI PEREMPUAN SEBAGAI TIM PENYUSUN RENCANA PEMBANGUNAN JANGKA MENENGAH DESA (RPJMD) DI DESA MATANG DANAU KECAMATAN PALOH KABUPATEN SAMBAS - Rena Rena; Karman Karman (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
In the Minister of Home Affairs Regulation Number 114 of 2014 concerning Village Development Guidelines, Preparation of Village Medium-Term Development Plans (RPJMD) involving all elements or stakeholders in the village which is held in a participatory manner through Musrenbangdes (Village Development Planning Consultation). It is stated in article 8 (4) that the drafting team must involve women. With this mechanism, it is hoped that women will be involved from the start in the development process starting from planning, implementation and evaluation as well as efforts to involve the community, including women in the decision-making process. This study uses empirical juridical research methods, namely examining the legislation in this context, namely the Minister of Home Affairs Regulation Number 114 of 2014 concerning Village Development Guidelines and looking at the condition of the facts found in the field, namely the Matang Danau Village government and women's participation. To obtain the data, the researcher used interview and observation guidelines. 114 of 2014 concerning Women's Participation as a Village Medium-Term Development Plan Development Team (Rpjmd) is appropriate and has included women and women's participation in the RPJMD drafting team, namely Preparing plans in Matang Danau Village as well as proposing improvements to farming roads and sewing courses.